Conservation Across Aquatic-Terrestrial Boundaries: Linking Continental-Scale Water Quality to Emergent Aquatic Insects and Declining Aerial Insectivorous Birds - Manning, David W. P.; Sullivan, S. Mažeika P. (Frontiers in Ecology and Evolution, 2021)
Larval aquatic insects are used to assess water quality, but less attention is paid to their adult, terrestrial life stage, which serves as an important food resource for declining aerial insectivorous birds. We used open-access water-quality, aquatic invertebrate, and bird-survey data to study how impaired water quality can emanate from streams and lakes through changes in aquatic insect communities across the contiguous United States. In general, the relative abundance of emergent insects was highest across the West, in northern New England, and in the Carolinas. The relative abundance of emergent insects declined with sedimentation, roads, and elevated ammonium concentrations in streams, but not lakes. The odds that a given taxon would be non-emergent increased by 1.7× as a function of pollution tolerance, underscoring the heightened sensitivity of emergent aquatic insects to water quality impairment. However, relationships between bird populations and emergent insects were generally weak for both streams and lakes. For streams, we observed the strongest positive relationships for a mixture of upland and riparian aerial insectivorous birds such as Western Wood-Pewee, Olive-sided Flycatcher, and Acadian Flycatcher and the strongest negative association for Purple Martin. Different avian insectivores responded to emergent insect abundances in lakes (e.g., Barn Swallow, Chimney Swift, Eastern Wood-Pewee, Common Nighthawk). In both streams and lakes, we observed stronger, but opposing, relationships between several aerial insectivores and the relative abundance of sensitive insect orders (E)phemeroptera, (P)lecoptera, and (T)richoptera (positive), and pollution tolerant individuals (negative). Overall, our findings indicate that emergent insects are negatively correlated with pollution tolerance, suggesting a large-scale loss of this nutritional subsidy to terrestrial environments from impaired aquatic ecosystems. While some bird populations tracked scarcities of emergent aquatic insects, especially EPT taxa, responses varied among species, suggesting that unique habitat and foraging behaviors likely complicated these relationships. Strengthening spatial and temporal concordance between emergent-insect and bird-survey data will improve our ability to interpret species-level responses over time. Thus, our analysis highlights the need for interdisciplinary research that develops new conservation and biomonitoring strategies focused on the repercussions of cross-ecosystem effects of water quality declines for threatened insectivorous avifauna and other terrestrial wildlife.